PENERAPAN APLIKASI QUIZIZZ PADA PESERTA DIDIK KELAS XI MIPA 3 UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI MATERI APBN DAN APBD DI SMAN 1 NGORO - Ngundiati, Nuryatim; Muhammad Basir; Riza Yonisa Kurniawan (FKIP Unswagati, 2023)
Economics learning aims to equip students with knowledge. With this goal, students are expected to be able to better understand each material taught as one of the provisions in their lives. However, in reality there are many students who have difficulty understanding the material taught in class, especially on APBN and APBD material. This is due to the lack of enthusiasm of students in teaching and learning activities. The lack of use of good learning methods also makes the classroom atmosphere monotonous and boring so that, it is revealed that the learning that has been taking place so far students are sleepy by putting their heads on the table, joking with their friends, and when the evaluation is carried out using paper tests students copy their friends' answers. So through this action research, researchers want to improve students' learning outcomes in economics learning, especially on APBN and APBD material by implementing the Quizziz application. The research subjects were class XI MIPA 3 students at SMAN 1 Ngoro, Ngoro sub-district, Mojokerto district for the 2022/2023 academic year, totaling 36 students. From the results of the learning activities that have been carried out for two cycles, and based on all the discussions and analyzes that have been carried out, it can be concluded as follows: Economic learning on APBN and APBD material with the application of the Quizizz application has a positive impact on student learning outcomes in class XI MIPA 3 SMAN 1 Ngoro, Ngoro sub-district, Mojokerto district for the 2022/2023 academic year. This is based on the post test scores which continue to increase from the first to the second cycle. This is evidenced by the increasing number of students who achieved KKM, the first cycle was 76.5% and the second cycle was 93%, an increase of 16.5%. This success was obtained by implementing the Quizizz application. By giving multiple choice questions to students through the Quizizz application, the questions will appear randomly on each student's screen so that the evaluation carried out can be purely according to the ability of the students